Clinical outcome following micro-vascular decompression for trigeminal neuralgia - Rao, Godugu Bhaskar; Maila, Sharath Kumar; Rao, Akyam Lakshman; Reddy, Ambarapu Mastan (International Journal of Research in Medical Sciences, 2017)
Background: Trigeminal neuralgia is the most common facial pain syndrome characterized by severe, brief recurrent episodes of electric shock like pain in the distribution of one or more branches of trigeminal nerve on one side of the face. In the present paper we present our experience with MVD for trigeminal neuralgia in a series of 20 patients during the last 4 years. Methods: All the patients presented to the neurosurgery department with features suggestive of Trigeminal Neuralgia during the last 4 years were evaluated with 3D FIESTA imaging. All those patients eligible for surgical decompression underwent a standard MVD in the form of a small retromastoid suboccipital craniotomy and Microvascular decompression done using a sheet of Teflon to intervene between the vessel and the Vth nerve. Any arachnoid bands across the nerve were carefully divided. Standard post-operative care given. The results were evaluated and tabulated. Results: 65% (N=13) of the patients had immediate postoperative relief. 15% (N=3) showed delayed but good pain relief in 3 weeks period. 20% (N=4) 20% pts did not show any pain relief at all post operatively. There were no mortalities in the series and no redo surgeries were performed in the series. Conclusion: Micro-vascular decompression is safe and effective in producing good pain relief over a long term in patients with Trigeminal neuralgias refractive to medical treatment.